Le rapport des bons élèves et des élèves en difficultés à la complexité de la philosophie : mesure de leur implication dans les DVP en fonction du niveau de compétences scolaires - Gabriela Fiema (Éducation et Socialisation)
This paper aims to study how the pupils’ school level influences their considering of philosophy for children workshops. To do that, the study of pupils’ reasoning and thinking during those workshops is necessary. The interlocutory logic is the methodological tool we used to analyze the pupils’ interactions and the quality of the philosophical reasoning. Our study is based on a group of six classes with different pupils’ ages. We will show in this paper how the philosophical workshops influence the production of philosophical reasoning of pupils with good results and pupils with bad results. We will answer the questions: the school results of pupils are linked with the quality of their reasoning? The fact that some pupils refuse the philosophy is due to their school results? Why a group of good pupils wanted to stop the philosophical workshops?